2011
DOI: 10.1375/ajgc.21.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Motivation, and Vocational Decision-Making of Australian Senior High School Students in Private Schools

Abstract: The purpose of this study was to investigate the roles of culture and motivation in the occupational decisions of senior high school students attending private schools. A theoretical framework guided the study. A questionnaire was administered to 492 Grade 11 students attending a stratified random sample of six independent (private) schools located in the Sydney (Australia) metropolitan area. Structural equation modelling was performed on the data collected. The major findings of the study centre on a new mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…These studies have indicated that interest and enjoyment of an occupation may be positively associated with a desire for intellectual stimulation and recognition from others, but negatively associated with the income that may be obtained from an occupation. Some differences appear to exist between the various elements of these career decision-making processes, and those that have been identified in the decision-making processes for adolescents in general, including considerations by intellectually gifted adolescents of a desire for intellectual stimulation and the fulfilment of potential (Jung & McCormick, 2011; Jung, McCormick, Gregory, & Barnett, 2011).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…These studies have indicated that interest and enjoyment of an occupation may be positively associated with a desire for intellectual stimulation and recognition from others, but negatively associated with the income that may be obtained from an occupation. Some differences appear to exist between the various elements of these career decision-making processes, and those that have been identified in the decision-making processes for adolescents in general, including considerations by intellectually gifted adolescents of a desire for intellectual stimulation and the fulfilment of potential (Jung & McCormick, 2011; Jung, McCormick, Gregory, & Barnett, 2011).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Furthermore, the differences within the same time interval may be attributed to cultural values and gender role differences in different cultures. Cultural orientation is one of the fundamental elements of career decision-making processes among adolescents Jung, McCormick, Gregory & Barnett, 2011). For instance, it was observed that girls were usually directed to career fields of medicine and education in Turkey (Bozgeyik, Doğan & Işıklar, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The six items that were designed to assess the valuing of the thoughts of family on general matters were originally adapted from scales used by Hui () and Brew, Hesketh, and Taylor (). The scale has been demonstrated to be valid and reliable (α = .83 in Jung et al., ; α = .84 in Jung & McCormick, ) on multiple occasions.…”
Section: Methodsmentioning
confidence: 96%
“…The six items that were designed to assess family influence on the occupational decision originated from items in a number of scales (Ajzen & Driver, ; Fitzmaurice, ) that were developed, refined, and psychometrically tested over two phases of data collection with 1,058 high school students (Jung & McCormick, ; Jung, McCormick, Gregory, & Barnett, ). The Cronbach alpha of the scale was high in Jung and McCormick (; α = .91).…”
Section: Methodsmentioning
confidence: 99%